Pembiasaan Berdo’a Sebelum Belajar dalam Meningkatkan Kecerdasan Sikap Spiritual (Studi Deskripsi di Rumah Belajar Al-Fatih Kota Serang) - Munawaroh Munawaroh; Sanin Sudrajat; Saepudin Saepudin; Hanafi Hanafi (Departement of Mathematics Education, 2024)
This study, conducted by researchers at Rumah Belajar AL-Fatih in Kota Serang, found that many students forget to say a prayer before studying, despite its numerous benefits. This is due to suboptimal planning, implementation, evaluation, and supporting and inhibiting factors. The purpose of this study is to understand the planning, implementation, and evaluation of the prayer routine, as well as the supporting and inhibiting factors and solutions for the prayer routine before studying in enhancing students' spiritual attitudes. This research uses a qualitative approach with a case study method and data collection techniques through observation, interviews, and document studies. The data sources are the head of Rumah Belajar Al-Fatih, teachers, and students. The results show that: First, in the planning aspect, the routine starts with setting goals, determining materials, programs, activities, and assessment tools. Second, the implementation is carried out individually in the classroom, with teachers guiding, providing examples, explaining the virtues, benefits, and proper ways of praying. Third, evaluations are conducted mid-semester, at the end of the semester, or at the end of the school year. The evaluation covers the planning, implementation, and outcomes of the routine. Fourth, supporting and inhibiting factors include the limited facilities and teachers available to guide. Overall, the prayer routine activities have been running smoothly, but spiritual intelligence has not yet been fully ingrained in all students due to inhibiting factors, such as students and teachers arriving late, as well as suboptimal discipline and understanding of the prayer routine.